Cover Image, Volume 50, Issue 6. Issue 6 (18th April 2018) - Vereecken, L.; Aumont, B.; Barnes, I.; Bozzelli, J.W.; Goldman, M.J.; Green, W.H.; Madronich, S.; Mcgillen, M.R.; Mellouki, A.; Orlando, J.J.; Picquet‐Varrault, B.; Rickard, A.R.; et al.
Abstract : On the cover : The cover image is based on the Research Article Perspective on Mechanism Development and Structure‐Activity Relationships for Gas‐Phase Atmospheric Chemistry, by Luc Vereecken et al., DOI: 10.1002/kin.21172 . Image Credit: Daniel Ellis and Andrew Rickard (University of York).